CONSTRAINTS TO AND OPPORTUNITIES FOR IMPROVING GOAT PRODUCTIVITY IN TABANAN REGENCY, BALI PROVINCE - L., Doloksaribu; Kayana, I. G. N.; Dewantari, M.; Dewi, G. A. M. K. (Majalah Ilmiah Peternakan; Vol 22 No 3 (2019): Vol. 22 No.3 (2019), 2019)
This study was undertaken to establish a database as consideration for improving goat production in Tabanan Regency. A survey was conducted from April to September 2018 on 38 smallholder goat farmers integrated with commodity plantations, owning 142 goats. Data were used to measure constraints to, challenges of, and opportunities for improving goat production, through a hybrid method of Strengths, Weaknesses, Opportunities and Threats and Analytic Hierarchy Process analyses. Problem priority faced was the competition between average numbers of 2.0 ± 0.1 family labourers aged 38.8 ± 2.1 years who cultivated average 0.9 ± 0.1 hectare of commodity plantations integrated with flock size of 2.5 ± 0.2 goats per household. Goats were housed in battery systems and fed forage. About 33% farmers had just sold all or portion of their goats due to the busy activity of clove and coffee harvesting in July-September and time consuming for cut and carry forage while commercial concentrates were not given to their goats. Recommendation taken was to providing Pennisetum purpureum silage as sustainable feed resource for goats thus improved the nutritious content of feed particularly during dry season where feed was limited or during harvesting and Bali Hindu ceremonies where family labourer was limited.